Women's experiences of sexual harassment in the retail clothing industry: a grounded theory study - Akbari, Maryam; Kaveh, Mohammad Hossein; Cousins, Rosanna (Frontiers in Psychology, 2024)
Introduction Sexual harassment is a significant problem in workplaces all over the world. Women's reactions to sexual harassment are influenced by various factors. The aim of the current study was to investigate how women respond sexual harassment in the retail clothing industry. Methods In-depth face-to-face interviews were conducted with 16 women aged 23–44 years (mean 29.18 years) employed for at least 3 years in clothes shops in Shiraz, Iran. A grounded theory approach was used to analysis the data and raise hypotheses. Results The main perpetrators of sexual harassment for female saleswomen were male customers. The women experienced conflict-induced stimulation (core phenomenon) when they were faced with sexual harassing behaviors (causal conditions). Such stimulation prompted three types of coping strategies: silence, avoidance, or confrontation. Intervening factors like the characteristics of the Iranian society (including family mores, state-imposed hijab regulations, patriarchal culture, educational system, and regulatory monitoring) and contextual factors (including individual and environmental factors and particularly employer expectations) were found to influence the selection of strategies used as well as their potential consequences in challenging situations. Conclusion The current study used a grounded theory approach to produce an explanatory storyline that can be tested. Sexual harassment induces conflict-induced stimulation and responses are influenced by intervening conditions, contextual factors, selected strategies, and the perceived consequences of the response. The findings of the grounded theory study suggest that there are negative consequences, particularly in terms of lack of employer support and losing one's job, shame, and family disapproval which act as barriers for female saleswomen to counteracting sexual harassment from male customers. Such an understanding can also be applied to develop educational policies to support women as well as ameliorate the prevalence of this essentially illegal problem.